Bou Hamara movement and its impact on the history of Al-Aqsa Morocco (1902-1909) (Journal of the College of Basic Education, 2022)
Perhaps the most important feature that distinguishes the history of many countries is the occurrence of many crises and rebellions after the death of every sultan or head of state and the claim of the owners of those rebellions that they have the right to seize power, and this is what happened with regard to the subject of our research.Bouhamara is considered one of the most prominent personalities who revolted and declared their rebellion against the Moroccan authority in the early twentieth century, as this person was able, with his ability to influence people's hearts, quickness of the eye, and his knowledge of magic, sorcery and astronomy, to declare his rebellion against the Moroccan sultan, taking advantage of the deteriorating political and economic conditions in the country As a result of the presence of a 13-year-old Sultan who does not know how to manage the affairs of the country, preoccupied with European games and innovations.